Trans-societal linkages of the Malaysian academic scientific community - Abu Hassan Othman (Universiti Kebangsaan Malaysia, 1979)
There now prevails a dual system of interacting internal and external relationships which differentially connect the scientific communities of developing countries with the world scene. As a result of these patterned relationships, the individual scientist is placed in social structures which socialize them, influence their reference groups and significant others, and generate new kinds of interpersonal networks with colleagues. This paper, therefore, attempts to discuss the paradigms of a third culture of science especially about two dimensions of the interrelations between the Malaysian academic scientific community and the world system of science.